Nas passagens das artes: conexões e assimetrias entre o cinema experimental e a vídeo-arte - Costa, Helton Luis Paulino da (2016)
From a new perception of the artist that will form before the whirl of changes that occurred after the Industrial Revolution, especially in scientific sectors (technicians and technologists) and social ones, the experimentation sense grows giddily toward abstraction in art, potentiating with the advent of moving pictures. Therefore, this study seeks to chronologically categorize certain focus of passing of arts, with emphasis on propositions so-called American underground cinema, that point to levels of connections and asymmetries specifically between the Experimental Film and the Video Art, systematically in the fields of film development and contemporary art, under the light of the “between-the-images” theory from the french theorist Raymond Bellour.